Exact travelling wave solutions for the local fractional two-dimensional Burgers-type equations. (15th January 2017) - Yang, Xiao-Jun; Gao, Feng; Srivastava, H.M.
Abstract: In this paper, a family of local fractional two-dimensional Burgers-type equations (2DBEs) is investigated. The local fractional Riccati differential equation method is proposed here for the first time. The travelling wave transformation of the non-differentiable type is presented. The non-differentiable exact travelling wave solutions for the problems are obtained. The present methodology is shown to provide a useful approach to solve the local fractional nonlinear partial differential equations (LFNPDEs) in mathematical physics.